Diogenész hordót keres . [Diogenes is looking for a barrel] - Révész, László (Videant Film Produkcio, 2005)
Verzio FF Submission Diogenes the Greek philosopher was, at one point in his life, living in a barrel. Drawing a parallel with Diogenes’ legend, the film documents the intellectuals who led a self-sufficient life but ended up homeless in the streets.